2008
DOI: 10.1124/dmd.108.022830
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C9-Catalyzed Metabolism ofS-Warfarin to 7-Hydroxywarfarin in Vivo and in Vitro in Chimeric Mice with Humanized Liver

Abstract: ABSTRACT:Chimeric mice having humanized livers were constructed by transplantation of human hepatocytes. In this study, we investigated whether these mice have a capacity for drug metabolism similar to that of humans by examining hydroxylation of S-warfarin, which is predominantly metabolized to S-7-hydroxywarfarin, catalyzed by CYP2C9, in humans but not mice. The 7-hydroxylating activity of chimeric mouse liver microsomes toward S-warfarin was approximately 10-fold higher than that of control (urokinase-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…Although no variant sequence was detected in the CYP2C9 gene (data not shown), real-time quantitative reverse transcription-PCR analysis revealed that the mRNA expression level of CYP2C9 in the hepatocytes was relatively low compared with that in other donor hepatocytes (data not shown). In fact, the plasma elimination of WAR in this study seems to be slower than that in the previous study using PXB mice transplanted with a different lot of human hepatocytes (Inoue et al, 2008). Therefore, the main reason for the failure to detect of CYP2C9 induction in the in vivo study was probably the low hepatic expression of CYP2C9 in the PXB mice used in this study.…”
Section: Discussioncontrasting
confidence: 46%
“…Although no variant sequence was detected in the CYP2C9 gene (data not shown), real-time quantitative reverse transcription-PCR analysis revealed that the mRNA expression level of CYP2C9 in the hepatocytes was relatively low compared with that in other donor hepatocytes (data not shown). In fact, the plasma elimination of WAR in this study seems to be slower than that in the previous study using PXB mice transplanted with a different lot of human hepatocytes (Inoue et al, 2008). Therefore, the main reason for the failure to detect of CYP2C9 induction in the in vivo study was probably the low hepatic expression of CYP2C9 in the PXB mice used in this study.…”
Section: Discussioncontrasting
confidence: 46%
“…In addition, it has been demonstrated that chimeric mice were able to generate humanspecific metabolites in vivo through primary and/or secondary metabolic reactions Inoue et al 2009;De Serres et al 2011). In agreement with these findings, in vitro studies using liver microsomes, cytosol and hepatocytes from chimeric mice have shown the formation of human selective metabolites (Aoki et al 2006;Inoue et al 2008;Kitamura et al 2008). It has been concluded that chimeric mice with humanized livers have the ability to achieve improved prediction of systemic metabolite exposure in humans when compared with conventional animal strains, providing metabolism is either completely or primarily hepatic (Kamimura et al 2010).…”
Section: Research Articlementioning
confidence: 55%
“…One approach which has the potential to address at least some of the inherent limitations of human in vitro biotransformation systems is to perform studies in vivo in "chimeric" mice with humanized livers, in which the majority of the hepatocyte population of the mouse liver has been replaced by human hepatocytes (Tateno et al 2004;Katoh and Yokoi, 2007;Okumura et al 2007;Inoue et al 2008;Inoue et al 2009;Strom et al 2010;Kamimura et al 2010;Chen et al 2011;De Serres et al 2011;Lootens et al 2011). These livers have been shown to express virtually the full complement of human Phase I and II metabolic enzymes and hepatic transporter proteins with gene-expression profiles and phenotypes similar (up to 85%) to those of the original donor liver (Tateno et al 2004;Yoshizato and Tateno, 2009;Strom et al 2010;Yamasaki et al 2010).…”
Section: Research Articlementioning
confidence: 97%
“…41) In their in vitro metabolism study using liver microsomes from chimeric mice, Inoue and her colleagues 42) found that warfarin-7-hydroxylase activity increased with increasing hepatic replacement ratio with human hepatocytes, and was markedly inhibited by the CYP2C9 inhibitor sulfaphenazole. They then administered (S)-warfarin to chimeric mice and analyzed the parent compound and its major metabolite in plasma.…”
Section: Successful Metabolism Studiesmentioning
confidence: 97%